Korean American Women's Community Activism and Their Response to Domestic Violence in Philadelphia - Kim, Su Kyung (2015)
Existing standard supportive services for domestic violence in the United States do not adequately address the cultural context for abused Korean immigrant women, and hence, results in further marginalization for this vulnerable population. For decades, Korean American women activists have been constructing support networks in their communities in response to this need. Nonetheless, scholarly literature has failed to capture the work and experiences of Korean American women activists who respond to and address domestic violence in their local community. Therefore, this study aims to give voice to one group of Korean American women activists and illuminate their experiences regarding domestic violence cases. In collaboration with a local Korean American women’s community activists association in one Northeastern U.S. city, this study explores their experiences with two data sources:(1) Korean counseling records of abused Korean immigrant women between 1986-2012, and (2) semi-structured interviews with the activists. Findings presented explicate the experiences of Korean American women activists focused on their response to domestic abuse within their community. This research can be used to guide the development of a model to provide contextually competent support for abused Korean American women in the U.S. and highlights the importance of collaboration between health care providers and ethnic minority community supportive services